PENGARUH PERSONAL SELLING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HERBAL HPAI DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI DI KOTA PEKANBARU - -, Kiki Karisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
In this modern era, the use of herbs as traditional medicines has been accepted in developed and developing countries, world attention to traditional medicines is increasing. This research aims to see the influence of Personal Selling and Product Quality on Purchasing Decisions for HPAI Herbal Products with Brand Image as a Mediating Variable in Pekanbaru City. The population in this study was all residents of Pekanbaru City. The sample collection technique used purposive sampling technique with a sample size of 109 people. The data collection technique uses a questionnaire where the research method used is a quantitative method. This research uses a data analysis method using SmartPLS (software) version 3.2.7. Analysis in PLS is carried out in three stages, namely Outer Model Analysis (Measurement Model), Inner Model Analysis (Structural Model) Hypothesis Testing. The results of this research show that Personal Selling influences Brand Image. Product quality influences brand image. Personal Selling influences purchasing decisions. Product quality influences purchasing decisions. Brand Image influences Purchasing Decisions. Personal Selling influences Purchasing Decisions through Brand Image. Product quality influences purchasing decisions through brand image Keywords: Personal Selling, Brand Image, Product Quality, Purchasing Decisions